System Study of Emission Control for Passenger Cars - Dehaven, Daniel L.; Platt, Allan B. (IEEE transactions on systems science and cybernetics, 1970)
The results of a total system analysis leading to the optimal design of an automotive exhaust air pollution control device are presented. The purpose is to demonstrate a capability for effectively optimizing design parameters of a subsystem in an operating environment which are subject to three optimality criteria: minimum cost for fixed performance; maximum effectiveness (emission reduction) per total cost dollar; and maximum society benefit per total cost dollar. The cost and performance models of the emission control device are developed. Controlled emissions of a representative vehicle are compared to federal standard levels and extrapolated to the population of vehicles assuming an inspection and maintenance policy. Total emissions are distributed in the air shed, and ground level concentrations are determined. These concentrations are compared with those of an uncontrolled population, and the average benefits of control are determined. The total costs to society of providing maintained control devices are compared to the benefits. Design optimization is performed based on the costs and benefits subject to objective function constraints using a general-purpose optimization language and computer executive SLANG/CUE.